Russia in the occupied territories of Ukraine : policies, strategies and their implementation - Petrov, Nikolaj V. (2024)
Zusammenfassung: Russia pushes for the "Russification" of the territories it occupies in Ukraine. Its policy is aimed at turning them into a military fortress against Ukraine. The declared aim of the economic restoration measures is to make the territories self-sufficient "parts of the Russian Federation". Their "integration" is by far the largest infrastructure project in current Russia. In the absence of tangible military successes, it is also the Kremlin's most important propaganda project. The Kremlin's actions in the occupied territories of Ukraine are like a second front in this war. Studying Russia's occupation policy is important both for understanding the actions of the invader and for developing action plans for the Ukrainian authorities after the end of the war and the liberation of these territories